Chinese traditional medicine (GuiZhi-ShaoYao-ZhiMu decoction) as an add-on medication to methotrexate for rheumatoid arthritis: a meta-analysis of randomized clinical trials. (February 2021) - Feng, Chenxi; Chen, Rongrong; Wang, Keer; Wen, Chengping; Xu, Zhenghao
Background: GuiZhi-ShaoYao-ZhiMu decoction (GSZD), a traditional Chinese herbal medication, has been frequently used as an add-on medication to methotrexate (MTX) for rheumatoid arthritis (RA) treatment in China. This meta-analysis evaluated the efficacy and safety of adding GSZD to MTX for RA treatment. Methods: We performed a systematic search of PubMed, Web of Science, EMBASE, and the Cochrane Library (all databases) for English-language studies and WanFang, VIP, and CNKI for Chinese-language studies up to 28 July 2020. Data from selected studies, mainly the response rates and rate of adverse events (AEs), were extracted independently by two authors, and a random-effects model (Mantel–Haenszel method) was used for the meta-analysis. Results: A total of 14 randomized controlled trials and 1224 patients were included (623 patients in the GSZD + MTX group and 601 patients in the MTX group). For efficacy, the meta-analysis found that combining GSZD with MTX increased the effective rate [relative risk (RR) = 1.24, 95% confidence interval (CI): 1.18–1.30, based on 1069 patients], defined as >30% efficacy, American College of Rheumatology 20, or a decrease of disease activity score 28 >0.6. Adding GSZD reduced the swollen and tender joint counts, the duration of morning stiffness, the levels of C-reactive protein and rheumatoid factor, and erythrocyte sedimentation rate. The adjuvant therapeutic effect of GSZD was independent of the dose of MTX or the combined utilization of other drugs in both groups. For safety, adding GSZD was associated with a lower rate of total AEs (RR = 0.46, 95% CI: 0.26–0.83, based on 615 patients) and gastrointestinal tract AEs (RR = 0.46, 95% CI: 0.24–0.88, based on 537 patients). Conclusion: Combining GSZD with MTX may be a more efficacious and safer strategy for treating RA compared with MTX alone. Further large studies are warranted to investigate the long-term efficacy and safety of adding GSZD to MTX for RA treatment.